Implementasi Pendidikan Akhlak Anak Usia Dini di Taman Kanak-Kanak Aisyiyah Bustanul Athfal Cakkela Kabupaten Bone - Qomaria, Nurul; Iting, Andi; Badu, Abd Rahman (Sipakatau: Jurnal Pendidikan dan Kebudayaan, 2024)
Implementation of early childhood moral education in Aisyiyah Bustanul Athfal Cakkela Kindergarten, Cakkela Village, Kahu District, Bone Regency. The purpose of this study was to determine the implementation of early childhood moral education in Aisyiyah Bustanul Athfal Cakkela Kindergarten, Cakkela Village, Kahu District, Bone Regency. To determine the supporting and inhibiting factors of children's moral education in Aisyiyah Bustanul Athfal Cakkela Kindergarten, Cakkela Village, Kahu District, Bone Regency. The data collection techniques used in this study were observation, interviews, and documentation. Based on the results of the study, it was concluded that the implementation of early childhood moral education in Aisyiyah Bustanul Athfal Cakkela Kindergarten, Cakkela Village, Kahu District, Bone Regency. consists of four kinds of things, namely saying polite words, shaking hands, apologizing if you are guilty or make a mistake, and saying thank you if given something. These four things are implemented through habituation activities both in the classroom and in the school environment. Supporting factors in the implementation of moral education in Aisyiyah Bustanul Athfal Cakkela Kindergarten, Cakkela Village, Kahu District, Bone Regency, namely a) educators are experts and professionals, have completed PAUD teacher education, attended workshops, training, briefings and routine coaching from the foundation. b) adequate facilities and infrastructure that support learning, c) availability of learning media, both traditional, simple, and modern. d) the condition of children who are enthusiastic and ready to learn. Meanwhile, the inhibiting factors for the implementation of moral education in Aisyiyah Bustanul Athfal Cakkela Kindergarten, Cakkela Village, Kahu District, Bone Regency, namely a) Different family backgrounds and environments. b) The potential, motivation, interests, problems, conditions, characters, and attitudes of each child are different. c) There are children who are active and difficult to condition. d) Children find it difficult to tidy up and return games to their place, so it takes quite a lot of time. e) The condition of parents who do not all provide further education to guide and accustom children at home. However, these inhibiting factors can be overcome by educators.